2021
DOI: 10.12998/wjcc.v9.i11.2619
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus infection with asymptomatic diffuse pulmonary disease in an immunocompetent patient: A case report

Abstract: BACKGROUND Cryptococcus presenting as an opportunistic pathogen mainly affects immunocompromised patients, but the disseminated form of infection is rare among immunocompetent populations. The partial radiographic characteristics of pulmonary cryptococcosis mimic lung carcinoma, leading to unnecessary open chest exploratory surgery, and the lack of a gold-standard noninvasive diagnostic increases the risk of misdiagnosis. Positron emission tomography/computed tomography (PET/CT), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The PC sections of GMS (+) and PAS (−) cases revealed a single or several Cryptococcus that were dispersed. Li et al (2021) reported a case of pulmonary cryptococcal infection in a patient with normal immune function and a small amount of fungi with positive GMS and negative PAS staining. In contrast, GMS staining with bright green counterstaining clearly revealed brown-black Cryptococcus against the green background.…”
Section: Discussionmentioning
confidence: 99%
“…The PC sections of GMS (+) and PAS (−) cases revealed a single or several Cryptococcus that were dispersed. Li et al (2021) reported a case of pulmonary cryptococcal infection in a patient with normal immune function and a small amount of fungi with positive GMS and negative PAS staining. In contrast, GMS staining with bright green counterstaining clearly revealed brown-black Cryptococcus against the green background.…”
Section: Discussionmentioning
confidence: 99%
“…Huang J et al reported a case series of eight patients with concomitant lung adenocarcinoma and cryptococcal pneumonia [14]. There have been other cases of similar presentation reported in the literature [15,16]. This may be due to the immune system of patients with adenocarcinoma not functioning the same way as that of a patient without cancer [17].…”
Section: Discussionmentioning
confidence: 99%